Analysis of the Development of Peer-to-Peer Lending in Indonesia and Its Impact on Financial Inclusion: A Literature Review - Larasati, Muti; Hasan, Dina Nurmala; Amelia, Fannisya; Gunawan, Ahmad (Indonesian Journal of Contemporary Multidisciplinary Research, 2025)
Advancements in technology have spurred the emergence of digital financial services innovations (fintech) such as peer-to-peer lending, which is rapidly growing in Indonesia, offering easily accessible financing alternatives. The purpose of this article is to analyze the development of peer-to-peer lending in Indonesia and its impact on financial inclusion in society. This research was conducted using a qualitative approach based on literature study. The findings show that peer-to-peer lending plays a role in increasing the reach of financial services for communities that have not yet accessed traditional banks, while also promoting inclusive economic growth. Although it has a significant positive impact, there are challenges or obstacles faced, such as bad loans, data breach threats, and frequently changing regulations. This research provides insights into the importance of regulatory support and financial education to maximize the benefits of peer-to-peer lending in enhancing financial inclusion in Indonesia.